Social Isolation’s Influence on Loneliness among Older Adults - Taylor, Harry Owen (Clin Soc Work J, 2019)
Social isolation and loneliness are significant risks to health among older adults. Previous studies have found a significant association between social isolation and loneliness; however, few studies examined the association between social isolation and loneliness in a multivariate context and how specific types of social isolation influence loneliness. This study fills this gap by examining social isolation’s overall influence on loneliness and how specific social isolation indicators influence loneliness. Data comes from 2014 Wave of the Health and Retirement Study, a nationally representative study of adults aged 50 and older. Social isolation was operationalized using seven indicators as social isolation from: 1) adult children, 2) other family members, 3) friends, 4) living alone, 5) being unmarried, and 6) not participating in social groups or 7) religious activities. Loneliness was operationalized by the Hughes 3-item loneliness scale. Loneliness was regressed on social isolation and key socio-demographic factors. Results found when social isolation indicators were combined into an index, every unit increase in overall social isolation was associated with an increase in loneliness. Furthermore older adults who were isolated from other family members and from friends, lived alone, were single, and did not participate in social groups or religious activities reported greater loneliness. Study findings demonstrate that greater overall social isolation and specific social isolation indicators are associated with greater loneliness. Clinical practice with older adults can be enhanced by understanding the connections between social isolation and loneliness and which forms of social isolation are more meaningful for perceived loneliness.